Building Schools for the Future: Lessons Learned From Performance Evaluations of Five Secondary Schools and Academies in England - Burman, Esfand; Kimpian, Judit; Mumovic, Dejan (Frontiers in Built Environment, 2018)
Building performance evaluations of five secondary schools and academies constructed under the Building Schools for the Future (BSF) programme in England found that CO₂ emissions associated with operational energy performance in all these buildings is higher than the median of the secondary schools. Whilst the new regulatory requirements for building fabric performance have led to some improvements in heating energy when compared against good practice and typical benchmarks, there is still significant discrepancy between heating energy use and the design expectations. Electricity use in these buildings is also 37-191% more than the median school and significantly worse than the design expectations. These results point to the importance of post-occupancy building fine-tuning and measurement and verification of performance in-use with respect to design projections to narrow the performance gap. It is also necessary to set out clear operational performance targets and protect energy efficiency measures from value engineering throughout building procurement and in operation to achieve good level of performance. Finally, it is suggested to adopt a holistic view of energy, environmental quality, and educational performance to have a better understanding of schools’ performance and potential conflicts between energy efficiency measures and indoor environmental quality.